Atorvastatin Use Associated With Acute Pancreatitis: A Case-Control Study in Taiwan. Issue 7 (February 2016) - Lai, Shih-Wei; Lin, Cheng-Li; Liao, Kuan-Fu
Abstract : Abstract: Few data are present in the literature on the relationship between atorvastatin use and acute pancreatitis. The aim of this study was to explore this issue in Taiwan. Using representative claims data established from the Taiwan National Health Insurance Program, this case–control study consisted of 5810 cases aged 20 to 84 years with a first-time diagnosis of acute pancreatitis during the period 1998 to 2011and 5733 randomly selected controls without acute pancreatitis. Both cases and controls were matched by sex, age, comorbidities, and index year of diagnosing acute pancreatitis. Subjects who at least received 1 prescription for other statins or nonstatin lipid-lowering drugs were excluded from the study. If subjects never had 1 prescription for atorvastatin, they were defined as never use of atorvastatin. Current use of atorvastatin was defined as subjects whose last remaining 1 tablet of atorvastatin was noted ⩽7 days before the date of diagnosing acute pancreatitis. Late use of atorvastatin was defined as subjects whose last remaining 1 tablet of atorvastatin was noted >7 days before the date of diagnosing acute pancreatitis. The odds ratio with 95% confidence interval of acute pancreatitis associated with atorvastatin use was calculated by using the logistic regression analysis. The logistic regression analysis revealed that the odds ratio of acute pancreatitis was 1.67 for subjects with current use of atorvastatin (95% confidence interval 1.18, 2.38), when compared with subjects with never use of atorvastatin. The odds ratio decreased to 1.15 for those with late use of atorvastatin (95% confidence interval 0.87, 1.52), but without statistical significance. Current use of atorvastatin is associated with the diagnosis of acute pancreatitis. Clinically, clinicians should consider the possibility of atorvastatin-associated acute pancreatitis when patients present with a diagnosis of acute pancreatitis without a definite etiology but are taking atorvastatin.